IDENTIFIKASI KESEHATAN TANAMAN BERKAYU DI KAWASAN KEBUN RAYA BANUA KOTA BANJARBARU KALIMANTAN SELATAN - Putri Ratih Sariati; Setia Budi Peran; Ahmad Yamani (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to observe type of  damage of  wood plants and analyze health, this study was conducted at  Banua Botanical Garden, Banjarbaru City, South Kalimantan. Some parameters are observed such as plant type, plant height, and damage conditions. This study uses  Purposive sampling method by taking  type that serves as  steering plant. The results showed that damage was found in leaves and discoloration caused by high light intensity, malnutrition and lack of routine maintenance. Protection is an effort  protect plants from various causes of damage. In line with this,  existence of protection is needed recognize as early  possible cause of  damage that occurs by identifying. Identify a process of recognizing plants that aims to find out  type in detail and damage. Damage is caused by biotic and abiotic factors, therefore it is necessary to recognize types of damage found, control alternatives and  introduction of forest health monitoring methods. The type of woody plant damage is damage that occurs in  part that shows an abnormal symptom or sign such as shoot death, open wound, leaf discoloration, broken and dead.Keywords: Identification; Damage; Woody Plants